Acculturation of Religious Rituals for Chinese Muslim Minorities in West Sumatra - Awiskarni, Awiskarni; Harmonedi, Harmonedi; Zalnur, Muhammad; Basit, Abdul (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to explore the acculturation and assimilation processes that ethnic Chinese in West Sumatra undergo upon converting to Islam, that the conversion does not lead to an outright abandonment of traditions. Utilizing a qualitative descriptive analysis approach, this research underscores how religious conversion fundamentally alters an individual's worldview and behavior. Converts to Islam are encouraged to earnestly learn and adhere to Sharia and Islamic teachings, initiating their spiritual journey with religious observances and distancing themselves from practices associated with their former beliefs. However, the conversion process is significantly influenced by one's environment, which plays a pivotal role in shaping the assimilation and acculturation experience of ethnic Chinese Muslims. This environment encompasses both familial and social contexts. The family environment, where individuals are connected by kinship—whether as children, spouses, or other familial roles—is marked by intensive interaction and communication. Yet, this close-knit communication does not necessarily guarantee a seamless conversion to another faith. Beyond the family, the surrounding social environment, including the workplace, extended family, and broader societal interactions, also impacts the conversion journey. Within these spheres, various factors either facilitate or hinder the process of embracing Islam for ethnic Chinese individuals. This study delves into these dynamics, examining the multifaceted influences on religious conversion and the subsequent negotiation between maintaining cultural heritage and adopting new religious identities. Through this analysis, the research seeks to contribute to a deeper understanding of the complex interplay between religion, culture, and identity among ethnic Chinese Muslims in West Sumatra